2020
DOI: 10.1111/jdi.13336
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between time in range, glycemic variability including hypoglycemia and types of diabetes therapy in Japanese patients with type 2 diabetes mellitus: Hyogo Diabetes Hypoglycemia Cognition Complications study

Abstract: Aims/Introduction Continuous glucose monitoring (CGM) metrics, such as times in range (TIR) and time below range, have been shown to be useful as clinical targets that complement glycated hemoglobin (HbA1c) for patients with type 2 diabetes mellitus. We investigated the relationships between TIR, glycemic variability and patient characteristics in patients with type 2 diabetes mellitus. Materials and Methods We carried out continuous glucose monitoring in 281 outpatients with type 2 diabetes mellitus who parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 39 publications
2
55
0
Order By: Relevance
“…Previous reports have shown that diabetic microvascular complications and vascular endothelial dysfunction are associated with TIR 70–180 deterioration 23–26 . The Advanced Technologies & Treatments for Diabetes stated that TIR is an appropriate and useful clinical target and outcome measurement that complements HbA1c for a wide range of patients with diabetes 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have shown that diabetic microvascular complications and vascular endothelial dysfunction are associated with TIR 70–180 deterioration 23–26 . The Advanced Technologies & Treatments for Diabetes stated that TIR is an appropriate and useful clinical target and outcome measurement that complements HbA1c for a wide range of patients with diabetes 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Beck et al 26 . reported that an HbA1c level of 7.0% corresponded to a TIR 70–180 of 64% in patients with type 1 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 eligible publications were retrieved in the full text, of which 4 did not meet inclusion criteria. Ultimately, we included 11 articles in our systematic review (Figure 1) (11-21). There was complete agreement between authors regarding article inclusion, risk-of-bias assessment, and data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, the ndings suggest that the predictive markers for hypoglycemia in patients with diabetes differ between elderly patients and adult patients of all ages. Recently, an observation study involving CGM for 281 adult type 2 diabetes outpatients aged 40-75 years, including 181 patients aged 65-70 years, revealed that low HbA1c level and use of hypoglycemic agents related to hypoglycemia including sulfonylureas, glinides and insulin were associated with high TBR [15]. Although the subjects in that study were aged < 75 years, our study enrolled older patients (> 75 years) to provide more re ective data for real-world clinical practice.…”
Section: Discussionmentioning
confidence: 99%